Hyaluronic acid ameliorates intervertebral disc degeneration via promoting mitophagy activation - Zhang, Fu; Wang, Songjuan; Gao, Manman; Li, Baoliang; He, Zhongyuan; Tang, Tao; Zhu, Zhengya; Liu, Shaoyu; Zhou, Zhiyu (Frontiers in Bioengineering and Biotechnology, 2022)
Activation of mitophagy was considered to be a potential therapeutic strategy for intervertebral disc degeneration (IDD). There was evidence suggesting that hyaluronic acid (HA) can protect mitochondria from oxidative stress in chondrocytes, but its protective effects and mechanism in nucleus pulposus cells (NPCs) remain unclear. This study aimed to confirm the effect of HA promoting mitophagy and protecting mitochondria function in NPCs, and explore its underlying mechanism. NPCs were treated with high molecular weight HA, tert-Butyl hydroperoxide (TBHP) and Cyclosporin A (CsA). Mitophagy, mitochondrial function, apoptosis, senescence and extracellular matrix (ECM) degradation were measured. Then, NPCs were transfected with C1QBP siRNA, mitophagy and mitochondrial function were tested. The therapeutic effects of HA on IDD by promoting mitophagy were assessed in bovine intervertebral disc organ culture model. The results showed that TBHP induced oxidative stress, mitochondrial dysfunction, NPCs apoptosis, senescence and ECM degradation. Treated by HA, mitophagy was activated, concomitantly, mitochondrial dysfunction, apoptosis, senescence and ECM degradation were ameliorated. Mitophagy inhibition by CsA partially eliminated the protective effects of HA against oxidative stress. After transfected with C1QBP siRNA to reduce the expression of C1QBP in NPCs, the effect of HA promoting mitophagy was inhibited and the protective effect of HA against oxidative stress was weaken. Additionally, HA alleviated NPCs apoptosis and ECM degradation in bovine intervertebral disc organ culture model. These findings suggest that HA can protect mitochondrial function through activation of mitophagy in NPCs and ameliorate IDD. Furthermore, C1QBP is involved in HA promoting mitophagy and protecting NPCs from oxidative stress. Taken together, our results provide substantial evidence for the clinical applications of HA in the prevention and treatment of IDD.